Students perception and understanding of the qalb : a phenomenological study of IIUM Institute of Education students - Erbhijakpor, Perkins Shuaibu Oghenenyerhovwo (Institute of Education, International Islamic University Malaysia, 2012)
The Qalb is a pervasive organ of cognition which is connected to the imaginative faculty of the soul; it has tremendous capacity for affecting intelligence and awareness and it can also become sick. A Muslim's status is defined by his or her submission to Allah and the organ which can be used to submit to the total will of Allah is the Qalb, because it is the organ devoted to morality, thought and intention. The purpose of this qualitative phenomenological research study was to explore the perceptions and understanding of the Qalb (the master organ of the human body, literally and figuratively) among the Institute of Education students of the International Islamic University Malaysia. Data for the study was elicited through interviewing and the procedure employed was qualitative. Data analysis was performed by using a phenomenological method which involved breaking the interview into themes, comparing the participants' experiences and determining the commonality among those experiences. Emergent themes included: the Qalb is the driver of the human body; A good Qalb leads to uprightness in man; It is only a Qalb in the state of Al-naf Al-Mutmainna that can bring forth good decisions; Qalb play a pivotal role in learning because all other organ obey its dictate; When behavior is not congruent with Quran's rhetoric's, Qalb is sick.